A new cohort of refugee students in Perth: Challenges for students and educators - Earnest, Jaya; Housen, Tambri-Anne; Gillieatt, Sue (The University of Western Australia, 2007)
Today's migration patterns have shifted in ways that bring new challenges to educators. New refugee arrivals in developed countries are an extremely diverse group. As a result, multiple approaches must be developed addressing the needs of diverse, multicultural and multilingual refugee and migrant populations. It has been clearly demonstrated that refugee children and adolescents are vulnerable to the effects of pre-migration, most notably exposure to trauma. In educational settings refugee students bring new challenges; many experienced educators are facing for the first time. The main aims of the project were to investigate and explore ways in which refugee adolescent youth perceive their experience of transition and resettlement into Australia and to examine the challenges faced by adolescent refugees in acquiring an Australian education. The research used a case study approach within a qualitative framework based on focus group interviews with 45 young refugees, school visits, in depth key informant interviews and accumulation of documentary data. The research approach interwove migration, resettlement and identity formation into an understanding of psychosocial wellbeing and educational experiences of adolescent refugees in Western Australia. This study argues that government departments (health, education and community development) need to work together to create a supportive and enabling environment to improve the wellbeing of refugee adolescents and provides preliminary recommendations for further research into strategies that will improve educational and mental health outcomes for these young people.